Hyporheic zone denitrification: Controls on effective reaction depth and contribution to whole‐stream mass balance. Issue 10 (7th October 2013) - Harvey, Judson W.; Böhlke, J. K.; Voytek, Mary A.; Scott, Durelle; Tobias, Craig R.
<x xml:space="preserve">Abstract</x> [1] Stream denitrification is thought to be enhanced by hyporheic transport but there is little direct evidence from the field. To investigate at a field site, we injected 15NO3−, Br (conservative tracer), and SF6 (gas exchange tracer) and compared measured whole‐stream denitrification with in situ hyporheic denitrification in shallow and deeper flow paths of contrasting geomorphic units. Hyporheic denitrification accounted for between 1 and 200% of whole‐stream denitrification. The reaction rate constant was positively related to hyporheic exchange rate (greater substrate delivery), concentrations of substrates DOC and nitrate, microbial denitrifier abundance (nirS), and measures of granular surface area and presence of anoxic microzones. The dimensionless product of the reaction rate constant and hyporheic residence time, λhzτhz define a Damköhler number, Daden‐hz that was optimal in the subset of hyporheic flow paths where Daden‐hz ≈ 1. Optimal conditions exclude inefficient deep pathways where substrates are used up and also exclude inefficient shallow pathways that require repeated hyporheic entries and exits to complete the reaction. The whole‐stream reaction significance, Rs (dimensionless), was quantified by multiplying Daden‐hz by the proportion of stream discharge passing through the hyporheic zone. Together these two dimensionless metrics, one flow‐path scale and the other reach‐scale, quantify the whole‐stream significance of hyporheic denitrification. One consequence is that the effective zone of significant denitrification often differs from the full depth of the hyporheic zone, which is one reason why whole‐stream denitrification rates have not previously been explained based on total hyporheic‐zone metrics such as hyporheic‐zone size or residence time.